Manajemen Keuangan Bagi Ibu Rumah Tangga Di Kelurahan Katimbang Kota Makassar - Fausiah Fausiah; Milka Pasulu; Pra Gemini; Nurdin Latif; Hapifah Hapifah; Aminah Aminah; Jumaidah Jumaidah; Nurmega Nurmega; Andi Irfan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
This community service was carried out in RT.01/RW.02, Katimbang City Village with the theme of financial management for housewives. The background for implementing the activity is because the level of understanding of housewives regarding the importance of planning and how to manage family finances is still lacking. The aim of this community service activity is to increase knowledge and abilities about planning and managing finances for housewives. The implementation of this service was attended by 25 participants on June 22 2023. The methods used were counseling, discussion and question and answer. The activity was carried out well, this was proven by the involvement of participants in participating in this activity from start to finish. After counseling is carried out, residents, especially housewives, will have high potential to encourage their families to have a better financial structure, households will be able to manage their finances well, have household fund reserves and be able to understand family financial management, including planning. controlling costs on household activities.